(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Cissus quadrangularis L. is a perennial herb belongs to Vitaceae. Traditionally used in the treatment of bone related issues such as Fracture, Pain, Inflammation, Osteoporosis, Rheumatoid and Osteoarthritis. The Preliminary Phytochemical screening indicates the presence of alkaloids, flavonoids, tannins, saponins and phenolic compounds. The aim of this study is to investigate the Phytochemical and Pharmacological evaluation of ethanol extract of Cissus quadrangularis L. In vitroDiuretic and Anti- inflammatory activity performed by using calcium oxalate method and Membrane stabilization assay. The extract of various concentrations were tested using cystone as positive control and 500,250,100,50 and 10 µg/L concentrations were prepared and performed. Results showed that the ethanol extract at concentration 500mg/ml effective against the inflammation and proved to treat the kidney stones as a diuretic.